Value averaging : the safe and easy strategy for higher investment returns - Edleson, Michael E. (John Wiley & Sons, 2007)
Michael Edleson first introduced his concept of value averaging to the world in an article written in 1988. To satisfy investor interest, he wrote a book entitled Value Averaging, which further detailed this method. Following the publication of the last edition of this highly sought after book in 1993, it has been nearly impossible to find--until now.